Regenerability of Turkish clinoptilolite for use in ammonia removal from drinking water - Turan, M.; Celik, M. S. (IWA Publishing, 2003)
Ion exchange methods using natural clay minerals such as zeolites exhibit a significant potential for the removal of ammonia from contaminated reservoir water or wastewater. The ammonia adsorption capacity of Gordes-Manisa (Turkey) clinoptilolite was studied in bottle adsorption tests and optimum adsorption conditions were established. Synthetic tap water made of NH 4 Cl and contaminated reservoir water, along with original and regenerated clinoptilolites, were used in a set of fixed ion exchange columns to identify the ability of clinoptilolite in the removal of ammonia. The breakthrough curves showed that increasing the influent ammonia concentration from 10, 15, and 20 mg/l concomitantly increased the effluent concentration and all the three curves exhibited a rapid rise after 125 bed volumes ( BV ). When C / C o reached 0.1, the BV was approximately 275 and 140 for 1–2 and 2–2.8 mm particle sizes, respectively indicating a larger adsorption capacity of the finer material. After running for 23 h, the C / C o values for the untreated, once-regenerated, twice-regenerated and thrice-regenerated clinoptilolites were 0.35, 0.06, 0.02, and 0.14 respectively. Twice-regenerated clinoptilolite showed the best performance compared with the others. The regeneration of clinoptilolite with 30 g/l NaCl solution at pH 11.5 was found to activate the clinoptilolite and increase the ion exchange performance. The breakthrough curves obtained under different conditions reveal that the untreated clinoptilolite adsorbs both the synthetic and reservoir water with the same ammonia concentration in a similar manner. These results indicate the potential of natural clinoptilolite for the removal of ammonia from contaminated reservoir water.